Robotic HIFU system for non-invasive breast cancer surgery - Chauhan, Sunita. (2008)
This document briefly describes the background and the formulation-to-implementation of a novel non-invasive robotic surgery system, named FUSBOT-(acronym for - Focal Ultrasound Surgery Robot for Breast Surgery). It also includes empirical set-ups and test jigs, functionality tests and in vitro and ex vivo trial results. The robotic system is designed and developed by the Bio-mechatronics group at RRC, NTU in order to assist surgery of breast tumours/cancers by the use of High Intensity Focused Ultrasound (HEFU). With carefully chosen HTFU dosage, it can ablate localized remote tissue structures, without harming the overlying normal tissues, and thus offers a potential modality for non-invasive surgery.